Factors affecting the timing of teething in healthy Turkish infants: a prospective cohort study - FIGEN SAHIN, AYSU DUYAN CAMURDAN, M. ORHUN CAMURDAN, AYSEGÜL OLMEZ, FATIH OZNURHAN, & UFUK B (IAPD and Blackwell, 2008)
Teething is a developmental process and occurs over a broad chronological age range. Genetic factors, gender and gestational age of the child, low birth weight, growth parameters, and nutritional status can influence eruption time of the primary teeth.